Prevalence of accidents and poisoning due to household hazardous materials in a rural area of Kancheepuram, Tamil Nadu - Ramanan Karunakaran, Shree; Muthunarayanan, Logaraj; Ramraj, Balaji (International Journal Of Community Medicine And Public Health, 2019)
Background: Over the last few decades hazardous materials have become a common household item in many rural areas of the developing world. Due to their easy availability, commercialization, accessibility and lack of awareness it has become a significant health problem globally. The objective of the study is to estimate the prevalence of household hazardous material accidents and poisoning and the factors associated with household hazardous accidents and poisoning among the rural population. Methods: A cross sectional study was done among the households located in rural fields practice area tertiary care hospital, with the sample size of 244 households by probability proportion sampling method. House to house interview was conducted using a predesigned, pre-tested questionnaire and household hazardous accidents and poisoning was assessed. Results: The overall prevalence of household hazardous accidents was 2.1% among the population. Among them 70% were less than 10 years of age followed by 10 to 20 years. The prevalence of household hazardous accident and poisoning was found to be positively associated with the factors like age <10 years, easy accessibility and storage in the open self. Conclusions: Regular assessment for household hazardous accident and poisoning should be carried out at the community level to find the exact burden. Utilization of this information, especially by the stakeholders and policy makers in the regional health sectors, can avert the problematic health situation.